Preliminary Investigation: Stearidonic Acid Production by Genetically Modified Saccharomyces cerreviseae Using Linseed Oil as A Fatty Acid Source - Kahar Muzakhar (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
Stearidonic acid (SDA); 18:4(n-3), an ω-3 Polyunsaturated Fatty Acid (PUFA), could be produced by Genetically Modified Saccharomyces cerreviseae (GMY) using Linseed Oil (LO) as fatty acid source. In nature, S. cerrevisae accumulates only very small amount lipid and contains until mono unsaturated fatty acids. But this GMY strain beside has capability to accumulate lipid, it also contains Δ6 desaturase gene which leads to convert α-Linolenic Acid (ALA); 18:3(n-3) to be SDA. Gas Chromatograph analysis of transmethylated LO sample showed that main component of fatty acid was ALA (about 57%), therefore LO can be used as a cheap source for other PUFA production. In order to provide ALA as a source for the yeast, enzymatic hydrolysis of LO using lipase was done. The lipase from Rhizomucor miehei (L4277-SIGMA) showed the highest activity among 5 lipases when 1 g/L LO in the medium for yeast (containing 6.7g/L yeast nitrogen base, 20 g/L glucose and 2.5g/L tergitol NP-40) was hydrolyzed. For SDA production, 1g/L LO in medium was aseptically hydrolyzed by lipase in 50 unit/mL for 18 hours at 30 oC and 140 rpm. The pre-culture of GMY (1% V/V) was then inoculated into the treated medium and 2.59 g/L dried cells were obtained after 5 days cultivation. ALA was accumulated in the cells at 0.06g/L (11% of total ALA in LO), and only 25% (0.015g/L) of accumulated ALA were converted to SDA. These results suggested that LO can be used as a source for PUFA production. In order to improve the productivity of SDA using GMY, hydrolysis of LO as well as cultivation condition and genetically improvement of the yeast must be highly considerated.